Noncommutative central limit theorem for Gibbs temperature states - Antoniouk, A. Vict.; Antoniouk, A. Val.; Kondratiev, Yu. G. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
For Gibbs temperature states, the scheme of the proof of the noncommutative central limit theorem is given by using the commutative central limit theorem for corresponding Euclidean measures. Applications are constructed for the model of a temperature-anharmonic crystal and the generalized Ising model with compact continuous configuration space.